Poetics of Transformation in Poetry of Adonis (Prilozi za orijentalnu filologiju, 2021)
One of the significant poetic characteristics of Ali Ahmad Said Esber, Adonis, regarded as the contemporary classic of Arabic poetry and thought, is the persistence on continuous transformation. This poetic principle is discussed and interpreted within complex imagery of the semantic pillar of Adonis’ poetry which is the myth of Tammuz. Adonis initially presents the myth of Tammuz in a veristic manner. However it is used only to deploy a continuous process of poetic semiosis in which the original myth will be variously (re)constructed, (re)contextualized and re-actualized. The result of this endeavour will be huge poetic value that will significantly mark the contemporary Arabic poetry as a whole.